Transarterial chemoembolization plus lenvatinib with or without programmed death-1 inhibitors for patients with unresectable hepatocellular carcinoma: A propensity score matching study - Guo, Peng; Pi, Xingtao; Gao, Feng; Li, Qiang; Li, Duqiang; Feng, Wendong; Cao, Wendong (Frontiers in Oncology, 2022)
Purpose: We conducted a retrospective study to compare transarterial chemoembolization (TACE) plus lenvatinib plus anti-programmed death-1 (PD-1) blockade with TACE plus lenvatinib in patients with unresectable hepatocellular carcinoma (HCC). Patients and methods: Patients with HCC were analyzed from January 2018 to January 2022 in three hospitals. Patients received TACE plus lenvatinib with or without anti-PD-1 antibodies (TACE+L+PD-1 or TACE+L, respectively). Baseline characteristics of the two groups were compared and propensity score matching (PSM) was performed. Overall survival (OS), progression-free survival (PFS), and objective response rate (ORR) of the two groups were compared. Adverse events in the two groups were analyzed. Results: A total of 166 patients were evaluated (TACE+L+PD-1, n=75; TACE+L, n=91). Before PSM, OS was prolonged in the TACE+L+PD-1 group (P=0.010), but PFS was similar between the two groups (P=0.18). ORR was higher in the TACE+L+PD-1 group (P=0.047). After PSM, estimated OS rates at 6, 12, and 24 months were 97.9%, 84.6%, and 74.1% respectively in the TACE+L+PD-1 group (n=48) and 93.1%, 66.1%, 43.4% respectively in the TACE+L group (n=48). Estimated PFS rates at 3, 6, and 12 months were 81.9%, 61.8%, and 30.9% respectively in the TACE+L group and 95.7%, 82.1%, and 68.4% respectively in the TACE+L+PD-1 group. OS, PFS and ORR were improved in the TACE+L+PD-1 compared to the TACE+L group (P=0.030; P=0.027; P=0.013). The safety of the TACE+L+PD-1 regimen was acceptable. Conclusions: The addition of anti-PD-1 immunotherapy to TACE+L significantly improved clinical outcomes in patients with unresectable HCC. Side effects were manageable.